3D Finite Element Modeling of GFRP-Reinforced Concrete Deep Beams without Shear Reinforcement - Markou, George; AlHamaydeh, Mohammad (My University, 2018)
This paper presents the numerical investigation of nine Glass Fiber-Reinforced Polymer (GFRP) concrete deep beams through the use of numerically-efficient 20-noded hexahedral elements. Cracking is taken into account by means of the smeared crack approach and the bars are simulated as embedded rod elements. The developed numerical models are validated against published experimental results. The validation beams spanned a practical range of varying design parameters; namely, shear span-to-depth ratio, concrete specified compressive strength and flexural reinforcement ratio. The motivation for this research is to accurately yet efficiently capture the mechanical behavior of the GFRP-reinforced concrete deep beams. The presented numerical investigation demonstrated close correlations of the force-deformation relationships that are numerically predicted and their experimental counterparts. Moreover, the numerically predicted modes of failure are also found to be conformal to those observed experimentally. The proposed modeling approach that overcame previous computational limitations has further demonstrated its capability to accurately model larger and deeper beams in a computationally efficient manner. The validated modeling technique can then be efficiently used to perform extensive parametric investigations related to behavior of this type of structural members. The modeling method presented in this work paves the way for further parametric investigations of the mechanical behavior of GFRP-reinforced deep beams without shear reinforcement that will serve as the base for proposing new design guidelines. As a deeper understanding of the behavior and the effect of the design parameters is attained, more economical and safer designs will emerge.
Keywords: GFRP rebars; Deep beams; Finite element method; Shear behavior